FOREIGN VOCABULARY MASTERING BY STUDENTS OF A TECHNICAL UNIVERSITY - Larisa Yurievna Zinovieva (Вестник Северо-Кавказского федерального университета)
The main features of foreign vocabulary mastering by students of a technical university are considered in the article. They are: practical orientation and successive nature of teaching in a technical university, high degree of generalization, self-contained work significance, speech activity kinds relationship peculiarities, active psychological support of cognitive processes such as contextual thought, attention, perception and memory.